The Krylov story: forming the ethics of professorship - Dmitry Tsigankov; Andrei Andreev; Pavel Naumov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The Krylov story, consequences of which are discussed in the letters of the trustee of Moscow school district Pavel Dmitrievich Golokhvastov to the minister of education, Count Sergei Semenovich Uvarov, can be read at diff erent levels and, depending on this, be subject to various scientifi c interpretations. One of the fi rst scholars who studied this topic, N. P. Barsukov, considered it to be a private family history, disassociated with the university environment, but, following religious discussions of T. N. Granovsky and A. I. Gertsen in 1845 and 1846, it is regarded to be undermining the unity of the circle of Westerners (Russ. западники). D. A. Tsygankov, on the contrary, sees the confl ict around Krylov as a landmark event in the history of the university which separates the era of the Great Disputes of the 1840s from the Dreary Seven Years («мрачное семилетие»). However, no matter how one evaluates Krylov’s story, there are practically no studies that would make the chronology of events associated with this confl ict more precise. The documents published below, together with documents that have already been made public but not suffi ciently studied, allow one to look at this university aff air in more detail. The Krylov story began in August 1846 and kept in tension all those involved up to the summer of 1848. This situation demonstrates that the university milieu is extremely confl ict-ridden, unpredictable, subject to abrupt changes.